Serological detection of cutaneous T-cell lymphoma-associated antigens - Eichmüller, Stefan B.; Usener, Dirk; Stein, Angelika; Thiel, Daniela; Schadendorf, Dirk (Proceedings of the National Academy of Sciences of the United States of America, 2001)
Cutaneous T-cell lymphomas (CTCL) are a group of skin neoplasms that originate from T lymphocytes and are difficult to treat in advanced stages. The present study is aimed at the identification of tumor-specific antigens from a human testis cDNA library using human sera known as the SEREX (serological identification of recombinantly expressed genes) approach. A cDNA library from normal testicle issue was prepared and approximately 2 million recombinants were screened with sera from Sézary Syndrome and Mycosis fungoides patients. A total of 28 positive clones belonging to 15 different genes/ORFs were identified, including five hitherto unknown sequences. Whereas control sera did not react with most clones, 11-71% sera from CTCL patients were reactive against the identified clones. Expression analysis on 28 normal control and 17 CTCL tissues by reverse transcription-PCR (RT-PCR) and Northern blotting revealed seven ubiquitously distributed antigens, six differentially expressed antigens (several normal tissues were positive), and two tumor-specific antigens that were expressed only in testis and tumor tissues: (i) A SCP-1-like sequence, which has already been detected in various tumors, has been found in one CTCL tumor and four sera of CTCL patients reacted with various SCP-1-like clones and (ii) a new sequence named cTAGE-1 (CTCL-associated antigen 1) was detected in 35% of CTCL tumor tissues and sera of 6/18 patients reacted with this clone. The present study unravels CTCL-associated antigens independent of the T-cell receptor. The SCP-1-like gene and cTAGE-1 were shown to be immunogenic and immunologically tumor-specific and may therefore be candidates for immunotherapy targeting CTCL.